Early development of the fetal central sulcus on 7.0T magnetic resonance imaging. Issue 48 (10th November 2015) - Zhang, Haidong; Zhang, Zhonghe; Yin, Xuntao; Zhan, Jinfeng; Zhao, Zhenmei; Tang, Yuchun; Liu, Chao; Liu, Shuwei; Zhong, Shizhen
Abstract: In the previous studies, the criterion for deciding the occurrence time of the fetal central sulcus (CS) on magnetic resonance imaging (MRI) is based on the observation by the eyes. There have been no existing quantitative standards or numerical criteria in this field. In this study, we reconstructed the three‐dimension (3D) images of the fetal brain based on the 7.0T MR images of 45 Chinese fetal specimens from the 11 to 22 weeks of gestational age (GA). Then we obtained data by measuring the maximum depth and length of the CS so as to analyze the early developmental pattern of it. These measures, especially CS depth, can be used to quantitatively determine the time of emergence of the fetal CS during the development. Statistics show that there are no gender or interhemispheric asymmetries of the CS from GA of 11 to 22 weeks.